Sixth- and Seventh-Order Rogue Waves for the Generalized (2 + 1)-Dimensional Kadomtsev-Petviashvili Equation - Zeng, Hang; Tang, Lu (Journal of Applied Nonlinear Dynamics, 2026)
A symbolic computation approach is employed to calculate rogue wave solutions in a bilinear equation with a controllable center, focusing on higher-order rogue waves of the generalized (2+1)-dimensional Kadomtsev-Petviashvili equation. The specific forms of the sixth- and seventh-order rogue waves of the KP equation have been obtained. The basic idea is to set the introduced parameters in the symbolic computation approach to 0 in order to simplify the calculation. Taking a third-order rogue wave as an example, some figures are given to shed light on the effect of the introduced parameters on the dynamic properties of the rogue waves by choosing appropriate values of the introduced parameters.